A Dynamic Journey from Futility to Productivity - Sankaran, Rajan; Shah, Jayesh; Shah, Meghna; Thakkar, Sneha; Shah, Devang (Homœopathic Links, 2014)
NEET (Not in Education, Employment or Training) is a major social worry in many countries. This article demonstrates how the Sensation Approach helps in individualising these cases so as to come to a Homeopathic simillimum. The varying methods of case taking in both cases and the results achieved thereby are illustrative of the depth of this Approach.
Keywords: Adolescents; Cultural disaffection; Depression; Sensation Approach; Synergy; Liliflorae; Lilium tigrinum; Naja tripudians